15N Hyperpolarization of Dalfampridine at Natural Abundance for Magnetic Resonance Imaging. Issue 55 (9th September 2019) - Skovpin, Ivan V.; Svyatova, Alexandra; Chukanov, Nikita; Chekmenev, Eduard Y.; Kovtunov, Kirill V.; Koptyug, Igor V.
Abstract: Signal Amplification by Reversible Exchange (SABRE) is a promising method for NMR signal enhancement and production of hyperpolarized molecules. As nuclear spin relaxation times of heteronuclei are usually much longer than those of protons, SABRE‐based hyperpolarization of heteronuclei in molecules is highly important in the context of biomedical applications. In this work, we demonstrate that the SLIC‐SABRE technique can be successfully used to hyperpolarize 15 N nuclei in dalfampridine. The high polarization level of ca. 8 % achieved in this work made it possible to acquire 15 N MR images at natural abundance of the 15 N nuclei for the first time. Abstract : FAM and fortune : A 32 000‐fold enhancement of the 15 N NMR signal (7.8 % spin polarization) was achieved for the biologically active molecule dalfampridine (FAM) by using a combination of the Signal Amplification By Reversible Exchange and Spin Lock Induced Crossing methods in a strong magnetic field. This major boost of the 15 N NMR signal allowed for the first time to obtain a 15 N MR image of FAM with a natural abundance of 15 N isotope.